A new species of Quilessa Fennah from Saint Martin (Fulgoromorpha: Fulgoroidea: Kinnaridae: Prosotropini) - Haas, Matthé Cornelis De; Bartlett, Charles R. (Zootaxa, 2024)
A new Kinnaridae species, Quilessa martinensis sp. nov. is described from Saint Martin in the Dutch Antilles. The new species differs from its congeners mainly in the shape of male genitalia, notably the shape of the aedeagus and anal tube. As in most other Quilessa species, the new species is an island-endemic. The high percentage of island-endemism suggests a higher species diversity in the Caribbean than is currently known.